HOSPITALIZED PATIENTS' AWARENESS OF THEIR RIGHTS-A CROSS SECTIONAL SURVEY IN A PUBLIC AND PRIVATE TERTIARY CARE HOSPITALS OF PUNJAB, PAKISTAN - Tabassum, Tahirah; Ashraf, Mariam; Thaver, Inayat (Journal of Ayub Medical College Abbottabad, 2016)
Background: The awareness of patient's rights is negligible in developing countries where no legal framework is present to protect these rights and Pakistan is no exception. Not only is there an absence of legal structure for protection of patients' rights, but the enforcement and implementation for existing law is also questionable. Pakistan has an Islamic Charter of Medical and Health Ethics which includes the medical behaviour and physician's rights and duties towards the patients. Despite all these charters on patients' rights, there is little to no awareness regarding these rights and their practice remains low in healthcare system of Pakistan. This assessment of awareness among patients about their rights will guide in formulating recommendations to improve the existing system of healthcare delivery in the country. Methods: This descriptive cross-sectional comparative study was conducted in two hospitals in Lahore, each belonging to public and private sector. A structured questionnaire was used to collect data from patients. A total of 220 patients were selected to participate in the study, 110 belonging to each private and public hospital. Results: The findings indicate that most of the patients (64%) were not aware of their rights. The awareness level was better in patients seeking care from private hospital than those from public hospital. Education, monthly income and type of hospital utilized were found to be positively associated with the level of awareness. Most of the patients were not satisfied with the practices of their rights, especially in public hospitals. Conclusion: The lack of awareness regarding the rights of a patient was more common in patients of public/government hospitals compared to private hospitals. A nation-wide healthcare education program is needed to increase awareness and practice of patients' rights in the country. Keywords: Patients' rights; Patients' care; awareness of patients' rights in hospitals